1290. Real-World Experience with Omadacycline for Nontuberculous Mycobacterial and Gram-Negative Infections: A Multicenter Evaluation. (31st December 2020) - Morrisette, Taylor; Philley, Julie V; Sigler, Carly; Frens, Jeremy J; Webb, Andrew J; Stevens, Ryan W; Howard, Catessa; Bouchard, Jeannette; Bookstaver, P B; Barger, Melissa; Lagnf, Abdalhamid M; Alosaimy, Sara; et al.
Abstract: Background: Omadacycline (OMC) is an aminomethylcycline antibiotic in the tetracycline class that has been Food and Drug Administration-approved for acute bacterial skin and skin structure infections and community-acquired bacterial pneumonia. OMC has been shown to have potent in vitro activity against a broad-spectrum of Gram-positive and Gram-negative organisms, as well as Nontuberculous Mycobacteria (NTM). Due to it's unique activity and availability as an oral agent, off-label use of OMC has been increasing. We evaluated the real-world effectiveness and safety of OMC for a variety of infections. Methods: This was a multicenter, retrospective, observational study that was conducted from January 2020 to June 2020. We included all patients ≥ 18 years of age that received OMC for ≥ 72 hours for any indication and/or pathogen. The primary outcome was clinical success, defined as a lack of 30-day (non-NTM) or 90-day (NTM) mortality or microbiologic recurrence and absence of therapy escalation or alteration. Reasons for OMC utilization and incidence of potential adverse effects attributable to OMC were also analyzed. Results: A total of 18 patients were included from six geographically distinct academic health systems (median age: 56 (IQR, 49-60.5) years; 61% male; 72% Caucasian). The majority of OMC use was in NTM (61%; 100% Mycobacterium abscessus ) and in Acinetobacter baumannii (22%) for bone/joint (39%) and respiratory tract (33%) infections. OMC was used primarily in the outpatient setting alone (83%) and most isolates did not have OMC susceptibility conducted (89%). Clinical success was reported in 83% of the total population (71% non-NTM and 91% NTM). The majority of patients were prescribed OMC due to antimicrobial resistance to previous antibiotic(s) (61%) and/or due to OMC's availability as an oral agent (44%). Three patients experienced side effects while on therapy (serum creatinine elevation, AST/ALT increase, and gastrointestinal distress). Conclusion: OMC appears to be effective and well-tolerated for a variety of infections caused by various pathogens, including M . abscessus and A . baumannii . Disclosures: Michael J. Rybak, PharmD, MPH, PhD, Paratek (Grant/Research Support)